Interface Direct Shear Tests on JEZ-1 Mars Regolith Simulant - Kexin Yin; Jiangxin Liu; Jiaxing Lin; Andreea-Roxana Vasilescu; Khaoula Othmani; Eugenia Di Filippo (Applied Sciences, 2021)
The mechanical behaviors of Martian regolith-structure interfaces are of great significance for the design of rover, development of excavation tools, and construction of infrastructure in Mars exploration. This paper presents an experimental investigation on the properties of a Martian regolith simulant (JEZ-1) through one-dimensional oedometer test, direct shear test, and interface direct shear tests between JEZ-1 and steel plates with different roughness. Oedometer result reveals that the compression and swelling indexes of the JEZ-1 are quite low, thus it is a less compressible and lower swelling soil. The cohesion and adhesion of JEZ-1 are lower than 5 kPa. The values of the internal friction angle range from 39.7° to 40.6°, and the interface friction angles are 16.7° to 36.2° for the smooth and rough interface. Furthermore, the direct shear and interface direct shear results indicate that the interface friction angles are lower than the internal friction angles of JEZ-1 and increase close to the internal friction angles with increasing interface roughness.